2002
DOI: 10.1289/ehp.021105
|View full text |Cite
|
Sign up to set email alerts
|

Starlink corn: a risk analysis.

Abstract: Modern biotechnology has dramatically increased our ability to alter the agronomic traits of plants. Among the novel traits that biotechnology has made available, an important group includes Bacillus thuringiensis-derived insect resistance. This technology has been applied to potatoes, cotton, and corn. Benefits of Bt crops, and biotechnology generally, can be realized only if risks are assessed and managed properly. The case of Starlink corn, a plant modified with a gene that encodes the Bt protein Cry9c, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(38 citation statements)
references
References 21 publications
(17 reference statements)
1
35
0
Order By: Relevance
“…This suggests that there was no human health risk associated with StarLink corn, supporting EPA's own assessment that Cry9C had a low probability of allergenicity (Bucchini, 2002). In contrast, there have been numerous examples during the 20 th century of foods imported into countries that have led to lifethreatening allergic responses, such as the case with kiwi fruit (Lucas et al, 2003).…”
Section: Low-level Presence Of Regulated Biotechnology Materialsmentioning
confidence: 76%
See 1 more Smart Citation
“…This suggests that there was no human health risk associated with StarLink corn, supporting EPA's own assessment that Cry9C had a low probability of allergenicity (Bucchini, 2002). In contrast, there have been numerous examples during the 20 th century of foods imported into countries that have led to lifethreatening allergic responses, such as the case with kiwi fruit (Lucas et al, 2003).…”
Section: Low-level Presence Of Regulated Biotechnology Materialsmentioning
confidence: 76%
“…The best known case in the United States is of Aventis' StarLink corn containing the Bt gene Cry9C. StarLink was approved by the EPA for animal feed but not for human consumption due to concerns that the stability of the protein under low pH might lead to allergic reactions (Bucchini, 2002). When traces of Cry9C were identified during 2000 in food products made from corn, there were rapid recalls of almost three hundred corn based products and Aventis spent approximately $100 million buying back corn that might have commingled with StarLink at a premium to try and remove StarLink from the market (Bucchini, 2002).…”
Section: Low-level Presence Of Regulated Biotechnology Materialsmentioning
confidence: 99%
“…In September 2000, it was reported and confirmed that StarLink had contaminated the human food supply. The basis for the approval process of StarLink only for animals was that it contained Cry9c, a protein from Bacillus thuringiensis (Bt), that appeared to be heat stable when compared with other Bt proteins and thus could not be excluded as an allergen (because allergenicity could not be ruled out), using an earlier version of the decision tree (Bucchini and Goldman 2002).…”
Section: Assessment Of Allergenicity To Genetically Modified Foods Anmentioning
confidence: 99%
“…Despite their rapid adoption by producers, some public and regulatory questions remain regarding the long term impacts of these products (NRC, 2002). In order to manage uncertainties surrounding these technological innovations, and in response to earlier breakdowns in the management of transgenic trait deployment and distribution (Bucchini and Goldman, 2002), considerable care has been taken to ensure confinement of products lacking full regulatory approval. Despite these efforts, incomplete compliance with regulatory conditions for confinement of transgenic crop field experiments can occur (USDA, 2004;USEPA, 2002).…”
Section: Introductionmentioning
confidence: 99%